THE PROGRAM “PHILOSOPHY FOR CHILDREN”: POSITIVE EXPERIENCE OF THE USA - Zahrebniuk, Yulia; Veremiuk, Liudmyla; Boichevska, Ilona; Ivanchuk, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Thе article deals with the peculiarities of theprogram “Philosophy for children” and possibility of its introduction at both junior schools and the lyceums in Ukraine. The aim of the article is to show the positive attitude of American educators to the program. The results of the research show that logical reasoning and intellectual creativity are not mutually exclusive, and can be formed within a single program. The authors claim that “Philosophy for children” program is undoubtedly relevant and needs not only active development but also promotion and dissemination among representatives of the academic philosophical community, educators, representatives of the relevant institutions of state power and general public.